PENGARUH PENGALAMAN AUDITOR, KOMPLEKSITAS TUGAS, TEKANAN KETAATAN, PENGETAHUAN AUDITOR TERHADAP AUDIT JUDGMENT (Studi Kasus Pada Kantor BPK RI Perwakilan Provinsi Jawa Tengah) - Ayu Lastari, 12.05.52.0039; Himawan, Arief (Students' Journal of Accounting and Banking, 2016)
The Audit Board of the Republic of Indonesia (BPK RI) Representatives of the Province of Central Java is representative of the BPK that has an important task to exercise control over the financial management of Java provincial government Tengah. Sehingga purpose of the CPC it self can be realized that the financial management of the State order, obey laws invitation to the results of the quality that can be utilized as needed. This study examined the effect of auditor experience, the complexity of the task, the pressure obedience, knowledge of auditors, and gender on audit judgment. This research was conducted at the Supreme Audit Agency Representatives of the Province of Central Java. Data used in this study, the primary data. Sources of primary data in this study were obtained directly from the auditors who worked at the Supreme Audit Agency Representatives of the Province of Central Java as many as 58 samples. By using multiple linear regression techniques. The results showed that the auditor's experience, the complexity of the task, the pressure obedience, knowledge and gender auditor positive and significant impact on decision making for the auditor to perform an audit judgment.  Keywords: Auditor Experience, Complexity of The Task, Pressure Obedience, Knowledge, Gender Auditor